2021
DOI: 10.1002/jcop.22550
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Experiential marketing: Will it affect customer citizenship behavior? An empirical study of multiple mediation model in Thailand

Abstract: The purpose of this study is to examine the consumer's experience of sense, feel, thinking, action, and relate experience in the shopping process whether the consumer is willing to voluntarily make beneficial behaviors for the enterprise. The study also aimed to assess the mediating effect of subjective well-being, brand identity, and received service fairness in the relationship between experimental marketing and customer citizenship behavior. Convenient sampling techniques were used to select samples. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 54 publications
1
8
0
1
Order By: Relevance
“…The purpose of this study was to evaluate the mediating effects of subjective well‐being, brand identity, and service fairness in the relationship between experimental marketing and customer civic behavior. It is necessary to understand the relationship between consumer shopping experience, consumer agent well‐being, brand identity, perceived service fairness, and customer civic behavior in online shopping platforms 16 . Even in the study of the impact of service recovery expectations and recovery definitions on customer civic behavior in the context of E‐commerce, customer civic behavior in the online shopping environment is critical to the success of E‐retailers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose of this study was to evaluate the mediating effects of subjective well‐being, brand identity, and service fairness in the relationship between experimental marketing and customer civic behavior. It is necessary to understand the relationship between consumer shopping experience, consumer agent well‐being, brand identity, perceived service fairness, and customer civic behavior in online shopping platforms 16 . Even in the study of the impact of service recovery expectations and recovery definitions on customer civic behavior in the context of E‐commerce, customer civic behavior in the online shopping environment is critical to the success of E‐retailers.…”
Section: Resultsmentioning
confidence: 99%
“…It is necessary to understand the relationship between consumer shopping experience, consumer agent well-being, brand identity, perceived service fairness, and customer civic behavior in online shopping platforms. 16 Even in the study of the impact of service recovery expectations and recovery definitions on customer civic behavior in the context of E-commerce, customer civic behavior in the online shopping environment is critical to the success of E-retailers. However, it is unclear whether and how service recovery expectations and recovery definitions predict customer civic behavior in the E-retail environment.…”
Section: Concerns and Importance About Customer Experience In The Cos...mentioning
confidence: 99%
“…, 2022). Similarly, Wang (2021) demonstrated in an online retailing context how superior online shopping experiences substantially impact the citizenship behavior of shoppers directed toward online retailers.…”
Section: Introductionmentioning
confidence: 94%
“…A recent study showed that value co-creation activities like the participation of customers in service design and resolving customers' problems increase customer repurchase intentions in online grocery retailing (Anshu et al, 2022). Similarly, Wang (2021) demonstrated in an online retailing context how superior online shopping experiences substantially impact the citizenship behavior of shoppers directed toward online retailers.…”
mentioning
confidence: 99%
“…(2015) tarafından gerçekleştirilen çalışmada, uçaklarda gümrüksüz ürünlerin sergilenmesi için tasarlanan deneyimlerin duygusal ve davranışsal deneyim türünün tüketicilerin duygusal tepkileri üzerinde etkileri olduğu ve bu durumun da anlık satın alma ve ağızdan ağıza aktarım üzerinde olumlu bir etkiye sahip olduğu sonucuna ulaşılmıştır. Tayland'da çevrimiçi alışveriş platformlarında gerçekleştirilen çalışmada deneyimsel pazarlama boyutlarının tümünün müşteri vatandaşlığı üzerinde pozitif etkilerinin olduğu sonucuna ulaşılmıştır (Wang, 2021). Jeon vd.…”
Section: Li̇teratür İncelemesi̇ Deneyimsel Pazarlama Alanındaki Teme...unclassified